Regulation of Mitochondrial Function by the Actin Cytoskeleton - Illescas, María; Peñas, Ana; Arenas, Joaquín; Martín, Miguel A.; Ugalde, Cristina (Frontiers in Cell and Developmental Biology, 2021)
The regulatory role of actin cytoskeleton on mitochondrial function is a growing research field, but the underlying molecular mechanisms remain poorly understood. Specific actin-binding proteins (ABPs), such as Gelsolin, have also been shown to participate in the pathophysiology of mitochondrial OXPHOS disorders through yet to be defined mechanisms. In this mini-review, we will summarize the experimental evidence supporting the fundamental roles of actin cytoskeleton and ABPs on mitochondrial trafficking, dynamics, biogenesis, metabolism and apoptosis, with a particular focus on Gelsolin involvement in mitochondrial disorders. The functional interplay between the actin cytoskeleton, ABPs and mitochondrial membranes for the regulation of cellular homeostasis thus emerges as a new exciting field for future research and therapeutic approaches.